Acute Heat Stress Changes Protein Expression in the Testes of a Broiler-Type Strain of Taiwan Country Chickens. Issue 2 (3rd April 2019) - Wang, Shih-Han; Cheng, Chuen-Yu; Chen, Chao-Jung; Chan, Hong-Lin; Chen, Hsin-Hsin; Tang, Pin-Chi; Chen, Chih-Feng; Lee, Yen-Pai; Huang, San-Yuan
ABSTRACT: Heat stress leads to decreased fertility in roosters. This study investigated the global protein expression in response to acute heat stress in the testes of a broiler-type strain of Taiwan country chickens (TCCs). Twelve 45-week-old roosters were randomly allocated to the control group maintained at 25°C, and three groups subjected to acute heat stress at 38°C for 4 h, with 0, 2, and 6 h of recovery, respectively. Testis samples were collected for hematoxylin and eosin staining, apoptosis assay, and protein analysis. The results revealed 101 protein spots that differed significantly from the control following exposure to acute heat stress. The proteins that were differentially expressed participated mainly in protein metabolism and other metabolic processes, responses to stimuli, apoptosis, cellular organization, and spermatogenesis. Proteins that negatively regulate apoptosis were downregulated and proteins involved in autophagy and major heat shock proteins (HSP90α, HSPA5, and HSPA8) were upregulated in the testes of heat-stressed chickens. In conclusion, acute heat stress causes a change in protein expression in the testes of broiler-type B strain TCCs and may thus impair cell morphology, spermatogenesis, and apoptosis. The expression of heat shock proteins increased to attenuate the testicular injury induced by acute heat stress.